Luminescence properties of natural dead sea salt pellet dosimetry upon thermal stimulation - Muhamad Azim, M. K.; Abdul Sani, S.F.; Daar, E.; Khandaker, Mayeen Uddin *; Almugren, K.S.; Alkallas, F.H.; Bradley, D.A. * (Elsevier, 2020)
In the event of a radiological accident or attack, immediate need arises for reliable estimation of dose to the population from an affected environment. This would contribute to proper medical treatment and any need for isolation of affected areas. As such, it is important to improve dosimetry assessment through use of locally available materials, the latter acting as accident/prospective dosimeters. Present investigation has examined the TL properties of natural salt collected in Jordan, from the Dead Sea, and exposed using 60Co gamma radiation. Entrance doses ranging from 2 to 10 Gy have been delivered, providing desirable luminescence features. Natural Dead Sea NaCl are produced in cylindrical pellet form, achieved with 0.1 and 0.3 cm thickness sized from the salt grains obtained by a compression force of 5.0 ± 0.1 tonnes. With these NaCl pellets, linear dose response has been achieved, producing strong TL yield for a 0.1 cm thick layer, exceeding that of 0.3 cm thickness by a factor of 3. The shape of the glow curves was found to be independent of delivered dose, the main TL dosimetric peak remaining within the range 180 °C to 280 °C and 300 °C to 400 °C for the 0.1- and 0.3 cm NaCl pellets respectively. Computerised glow curve deconvolution was carried out, comprising of ten peaks, with associated activation energies and frequency factors. TL response per unit mass of NaCl pellets for both thicknesses were found to be energy dependent, predominating in yield at 60 keV. Over a period of 35 days the 0.3 cm NaCl pellet showed the least effect of fading, with loss of TL signals of 56% compared to an 81% loss for the 0.1 cm pellet. It is also noted that the combination of low activation energy and high frequency factors for the electrons to escape a trap for the 0.1 cm NaCl pellet samples subjected to 2 Gy gamma irradiation resulted in a highly substantial loss of TL signal over the first 7 days in comparison to the 0.3 cm NaCl pellet. Both samples thicknesses were unable to produce reproducible TL responses for the second and greater use. It has also been found that in addition to particle size, moisture and pre-irradiation annealing influence the TL properties. The excellent TL properties achieved by 0.1 cm NaCl pellets indicate their potential use as an accident/prospective dosimeter.